Ultrafast alkaline deep eutectic solvent pretreatment for enhancing enzymatic saccharification and lignin fractionation from industrial xylose residue. (May 2022) - Ma, Cheng-Ye; Xu, Ling-Hua; Sun, Qian; Sun, Shao-Ni; Cao, Xue-Fei; Wen, Jia-Long; Yuan, Tong-Qi
Graphical abstract: Highlights: Ultrafast alkaline DES pretreatment was developed for fractionation of xylose residue. The precipitation of lignin and recovery of DES was achieved by injecting CO2 . Recovered alkaline DES still had distinguished pretreatment performance. The obtained DES lignin nanoparticles (LNPs) had excellent antioxidant activity. The highest glucose yield (90.12%) had been achieved under the mild condition. Abstract: An aspirational pretreatment method for efficient fractionation and tailored valorization of large industrial biomass can ensure the realizability of sustainable biorefinery strategies. In this study, an ultrafast alkaline deep eutectic solvents (DES) pretreatment strategy was developed to efficiently extract the lignin nanoparticles and retain cellulose residues that could be readily enzymatic saccharified to obtain fermentative glucose for the bioenergy production from industrial xylose residue. Results showed that the DES pretreatment had excellent delignification performance and the regenerated DES lignin nanoparticles exhibited well-preserved structures and excellent antioxidant activity, as well as low molecular weights and relatively uniform size distribution, which could facilitate downstream catalytic degradation for production of chemicals and preparation of lignin-based materials. Under the optimal condition (DES pretreatment: 80 °C, 10 min; saccharification: 10 FPU/g, 5 wt%, 100 mg/g Tween 80), the glucose yield of 90.12% could be achieved, which was dramatically increased compared to raw materials.